De la collecte des traces d'interaction à la publication scientifique - Matthieu Cisel (Centre National d'Enseignement à Distance, 2022)
In this contribution, which takes the form of a return of experience, we return to the role that the rise of MOOCs has played in the multiplication of studies mobilising interaction traces (learning analytics in English). By reaching unprecedented scales in terms of the number of learners tracked, studies based on these data have gained legitimacy and have been able to reach the most prestigious scientific journals. We argue that this success should invite further work to study the behaviour of large numbers of users of online platforms. Because of the wealth and volume of data they produce, French educational platforms could give French research an international dimension. After mentioning FUN MOOC, we will illustrate our point by looking at LMSs such as Moodle, taking the example of M@gistère. Ambitions in this field nevertheless come up against a series of obstacles, notably technical, legal and ethical. The common thread that we follow to illustrate ambitious analyses lies in the articulation between the registration behaviour of users within a course catalogue and their use of the training once they have registered.